2018
DOI: 10.15407/ubj90.06.097
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of N-stearoylethanolamine on memory disorders, blood and brain biochemical parameters in rats with experimental scopolamine-induced cognitive impairment

Abstract: The impairment of cognitive functions is the most studied medical and social problem nowadays. The aim of this study was to evaluate the protective effects of n-stearoylethanolamine (nSe) on memory state, blood and brain biochemical parameters in rats under scopolamine-induced cognitive impairment. The results of this study shown that nSe administration to rats per os (5 mg/kg, 5 days, during last 3 days nSe was administrated 20 min prior to scopolamine injection (1 mg/kg, once daily for 3 days, intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Previous experiments demonstrated neuroprotective effect of NSE in the model of chronic morphine dependence [52,53] and its anti-acetylcholine esterase and pro-cognitive activity in the model of cholinergic deficiency caused by scopolamine [54]. We also showed that NSE restored memory and α7 nAChR content and stabilized mitochondria in the brains of WT mice either injected with LPS or immunized with the α7 extracellular domain (1-208) [22].…”
Section: Discussionsupporting
confidence: 70%
“…Previous experiments demonstrated neuroprotective effect of NSE in the model of chronic morphine dependence [52,53] and its anti-acetylcholine esterase and pro-cognitive activity in the model of cholinergic deficiency caused by scopolamine [54]. We also showed that NSE restored memory and α7 nAChR content and stabilized mitochondria in the brains of WT mice either injected with LPS or immunized with the α7 extracellular domain (1-208) [22].…”
Section: Discussionsupporting
confidence: 70%
“…The main ones are superoxide dismutase, catalase, glutathione peroxidase, and glutathione. Auxiliary enzymes include glutathione reductase, glutathione S-transferase, and glucose-6-phosphate dehydrogenase, as well as metal-binding proteins: transferrin, ceruloplasmin and albumin, vitamins: alpha-tocopherol, ascorbate and beta-carotene, flavonoids and urates [27]. Glutathione reductase is an enzyme that reduces glutathione disulfide to glutathione with the participation of NADPH.…”
Section: Discussionmentioning
confidence: 99%